An ecofeminist analysis of environmental justice in South Africa: Mpumalanga Highveld and Cape Town region - Mamoepa, Bohlale Mashaa (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.